SEKOLAH YAYASAN KESEJAHTERAAN PEGAWAI PERTAMINA DI KOTA JAMBI 1952 – 2000 - Reky Hadi Susanto, Ujang Hariadi (Universitas Batanghari Jambi, 2017)
Abstra The purpose of this research is to describe the process of establishment and development of YKPP School, as well as to explain the role or contribution of YKPP School for the advancement of education in Jambi City as well as to improve the economic welfare of the parties directly involved in the management and operation of the school. The research method used is the method of history ranging from heuristic stages, criticism, interpretation, and historiography. The approach used is sociology approach and prosessual approach. The result showed Initially YKPP (elementary and junior high school) schools showed progressive and progressive conditions, but since 2000 there has been a significant deterioration of both schools, especially after they are no longer under the auspices of Jambi Pertamina, and taken over by their respective school committees. The setback is mainly seen from the number of students, the provision of new facilities and learning infrastructure. Nevertheless both schools survive and keep trying to maintain the quality of schools, teachers, and students. In terms of quality, the school still earns accreditation status with rank A and B, in terms of teachers still graduated S1 with various new disciplines, and students who continue to get achievements in various fields (art, sport, scout, science, and others).Keywords: School, YKPP, Kota Jambi, Progress,